PENGARUH MOTIVASI DAN INSENTIF TERHADAP KINERJA KARYAWAN MELALUI KOMITMEN ORGANISASI PADA SENYUM MEDIA STATIONARY JEMBER - Rasyid, Mohammad Nurhasan; Tobing, Diana Sulianti; Syaharudin, Mohamad (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2016)
Abstract: This study was done to analyze whether the motivation and incentives affect the performance of organizational commitment and performance, as well as the influence of commitment to employee performance media smile Stationary Jember. The research design used in this research is quantitative. The study population was all employees of Smile Media Stationary meaning of this research study respondents census with 76 employees. Methods of data analysis used in this study is the path linear regression analysis. The results of this research are formal education, work environment and work experience simultaneously significant effect on performance. In partial formal education and the work environment does not significantly influence performance. Meanwhile, work experience variable partially significant effect on employee performance.Keywords: employee performance, organizational commitment, incentives, dan motivation